ANALISIS PENGARUH KEDISIPLINAN DAN LOCUS OF CONTROL TERHADAP KINERJA DENGAN MOTIVASI SEBAGAI MEDIASI (STUDI PADA PEGAWAI NEGERI SIPIL DI RUMAH SAKIT UMUM DAERAH KABUPATEN BATANG ) - Yanti Wahyuningsih, 10.42.02.0119 (Students Journal of Economic and Management, 2013)
The objective of this research is to analyze the effect of discipline and locus of control on the performance of employees with motivation as mediation. The research methodology used is quantitative explanative with a path analysis model, to test the coefficient of determination, and looking for a correlation coefficient. The research was conducted at the General Hospital Batang, with a sample of 148 employees. Sampling using purposive sampling method sampling with specified criteria. The results of this research are as follows: (1) Disciplinary has direct effect and significant on work motivation; (2) Locus of control has direct effect  and a significant on work motivation; (3) Disciplinary has direct effect  and significant on employee Performance; (4) Locus of control has a direct and significant impact on employee performance, and Locus of control also has an indirect effect on employee performance through the mediation of Work Motivation; (5) Work motivation has a direct and significant impact on employee performance. Therefore, employee performance improvement can be done through increased discipline, locus of controll, and work motivation. Keywords: discipline, locus of control,  motivation,  performance of employees, path analysis,